2000
DOI: 10.1016/s0893-133x(00)00122-6
|View full text |Cite
|
Sign up to set email alerts
|

Increased CSF Volumes Are Associated with Diminished Subjective Responses to Cocaine Infusion

Abstract: We evaluated the hypothesis that ventricular and cortical CSF volume increases are associated with reductions in the magnitude of euphoric effects produced by intravenous IV cocaine infusion in cocaine dependent (CD) individuals. Eleven CD patients participating in a cocaine-infusion study and eleven control subjects underwent magnetic resonance imaging (MRI). Two CSF regions of interest (lateral ventricles and frontal cortex CSF) and two comparison regions (third ventricle and posterior cortex CSF) were mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
2
8
0
Order By: Relevance
“…These results agree with those of most previous studies that reported that global brain atrophy does not follow cocaine addiction [37-39; but see 40, 41]. …”
Section: Discussionsupporting
confidence: 93%
“…These results agree with those of most previous studies that reported that global brain atrophy does not follow cocaine addiction [37-39; but see 40, 41]. …”
Section: Discussionsupporting
confidence: 93%
“…CSF enlargement is also consistent with adult cocaine or alcohol abuse and suggestive of response to neuronal injury. Cocaine-dependent adults exhibit increased cortical CSF volume (Bartzokis et al 2000). Alcohol-related GM and WM loss is linked to enhanced CSF volumes, which decrease proportionally with longer abstinence (Demirakca et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that age-related decreases in levels of cocaine-induced euphoria correlate with regional brain volume reductions (4,5). In a study of intranasal cocaine self-administration, the number of episodes of cocaine use in one’s lifetime was positively correlated with anxiety after cocaine administration (6).…”
Section: Introductionmentioning
confidence: 99%